Fotografi: Sains, Teknologi, Seni, dan Industri - Harsanto, Prayanto Widyo (Nirmana, 2011)
The digital photography era is a great development in science and technology in the history of photography after Niepce and Daguerre. Where in the 19th century, their experiments lead to the ability to capture images permanently with the subject of a cityscape in France. This discovery was considered most perfect in photography compared to previous ones. In the digital camera era, society views photography as something easy, inexpensive, and a part of everyday life. This is what is called the digitalization of photography. However so sophisticated the photographic equipment there may be today, there is still the need a photographer that has the knowledge and technical skills with good aesthetic sensibilites as â€œthe man behind the camera.â€ In the era of creative industry like today, photography can be said to be in four aspects, which are sciense, technology, art, and industry, that are intertwined. It is because photography is not as easy as pushing the shutter button, even more so in the world of education. The teaching of photography cannot be seen as merely teaching techniques, adjusting apertures, speed, and lighting, but it involves the eyes, thoughts (knowledge and understanding), and feeling in selecting an object and arranging it in a frame of a photograph. Furthermore, what should be considered is that besides teaching how to produce and create a photo, one should know and understand as to every possibilites of aspects of its distribution after the photo has been successfully produced.